2013
DOI: 10.1183/09031936.00129312
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the lifetime risk of COPD exacerbation requiring hospitalisation

Abstract: This study aimed to estimate time trends in the lifetime risk of hospitalisation with exacerbation of chronic obstructive pulmonary disease (COPD) in Denmark.During the period from 1994 to 2008, a register-based cohort study was conducted covering each subject in the entire population of Denmark (5.18 million in 2008). Based on previously validated diagnosis codes, all COPD hospitalisations were identified. Individual retrospective review periods of 8 years were used to determine first-time hospitalisations. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In this cohort study, we found that one in two individuals in this remote community had hospital‐diagnosed COPD during their lifetime. The lifetime risk in this Aboriginal group is much higher than those previously reported in non‐Indigenous populations 8–11 . In Ontario, Canada, Gershon et al reported about one in four people in the general population will develop physician‐diagnosed COPD in their lifetime 8 .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In this cohort study, we found that one in two individuals in this remote community had hospital‐diagnosed COPD during their lifetime. The lifetime risk in this Aboriginal group is much higher than those previously reported in non‐Indigenous populations 8–11 . In Ontario, Canada, Gershon et al reported about one in four people in the general population will develop physician‐diagnosed COPD in their lifetime 8 .…”
Section: Discussionmentioning
confidence: 65%
“…In this study, we found that women had a higher lifetime risk of hospital diagnosed COPD than men. In studies in Canada and Netherlands, men had a slightly higher lifetime risk than women 8 while, in a Denmark study, women had slightly higher lifetime risk of COPD (Figure ) 11 . These differences can be partly explained by sex differences in the prevalence of smoking among different populations.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…According to the only validation study [10] and in line with prior studies [6,11,12], hospitalisation with COPD was defined as any hospitalisation with either ICD-10 codes J41-44 as primary diagnosis or with J13e18 (pneumonia) or J96 (respiratory failure) as primary diagnosis combined with J41-44 as a secondary diagnosis. The individual health administrative data were linked with data from the Demographic Register regarding the patients' dates of birth, death, and migrations to or from Denmark.…”
Section: Setting and Datamentioning
confidence: 99%